Bulog's Strategy In Rice Export-Import Amid Food Security Issues In Indonesia 2023-2024 - Vani Khairunissa; Ihsan Wahidin; Cut Lisa Miranda; Taswiah Asma; Diana Usmara (Trasearch (Training, Research and Academy Society, 2025)
Food security is a strategic issue for Indonesia, considering global challenges such as climate change, economic instability, and geopolitical conflicts that impact the food supply chain. Perum Bulog, as the institution responsible for national food logistics, plays a crucial role in maintaining price stability and food availability through rice export-import strategies. However, differences between domestic and international rice prices, along with high production costs, pose challenges to improving Indonesia’s competitiveness in the global market. This study employs a literature review method to analyze Bulog’s export-import policies from 2023 to 2024. The findings reveal that Bulog implements strategies such as increasing government rice reserves, optimizing distribution, and fostering partnerships with local farmers to strengthen national food security. With appropriate policies and government support, Indonesia is expected to achieve rice self-sufficiency by 2025 and enhance its competitiveness in international markets.